ҚАРАҚАЛПАҚ БАЛАЛАР ӘДЕБИЯТЫНЫҢ РАЎАЖЛАНЫЎЫНА ДҮНЬЯ БАЛАЛАР ӘДЕБИЯТЫНЫҢ ТӘСИРИ - Қазақбаев, C.; Бийсенбаев, Қ. (FAN va JAMIYAT, 2021)
The article examines the influence of world literature on the development of Karakalpak children's literature in the late ХХ th century. The stages of emergence, formation and development of lyrical, epic, dramatic genres are studied.